Proceedings of the 1st Paris Van Java International Seminar on Health, Economics, Social Science and Humanities (PVJ-ISHESSH 20 2021
DOI: 10.2991/assehr.k.210304.026
|View full text |Cite
|
Sign up to set email alerts
|

Educating with Paying Attention to Individual Differences: Case Study of Slow Learner Students in Inclusion School

Abstract: Each student has a uniqueness that must be considered by the teacher in the learning process, unusually slow learner children with various peculiarities. This study aims to reveal the attention of Islamic Religious Education teachers to slow learner children. This study is qualitative research with a survey approach-data sources of Islamic religious education teachers in inclusive schools with their specificity of slow learner students. Through in-depth interviews, the data is extracted from the source. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…Metode yang digunakan dalam pelaksanaan Pengabdian kepada masyarakat (PKM) ini disesuaikan dengan dunia anak yaitu sosiodrama. Pertimbangan penggunaan teknik sosiodrama adalah secara psikologis seorang anak akan senang melakukan aktivitas bermain peran [12]. PKM ini dilaksanakan bekerja sama dengan pengelola Taman Pendidikan Al-Qur'an.…”
Section: Metodeunclassified
“…Metode yang digunakan dalam pelaksanaan Pengabdian kepada masyarakat (PKM) ini disesuaikan dengan dunia anak yaitu sosiodrama. Pertimbangan penggunaan teknik sosiodrama adalah secara psikologis seorang anak akan senang melakukan aktivitas bermain peran [12]. PKM ini dilaksanakan bekerja sama dengan pengelola Taman Pendidikan Al-Qur'an.…”
Section: Metodeunclassified
“…Beranjak dari permasalahan di atas maka dirasa perlu untuk melakukan asesmen kesiapan dan penyebab motivasi rendah dalam belajar. Guru harus merespon perbedaan siswa d alam proses pembelajaran, agar pembelajaran menjadi efektif (Ru'iya et al, 2021). Dalam rangka merespon perbedaan siswa, guru perlu mempertimbangkan teori multiple intellegences yang mengatakan bahwa manusia mempunyai banyak kecerdasan yang dapat digunakan untuk memecahkan masalah dalam kehidupannya.…”
Section: Pendahuluanunclassified
“…Based on some of these opinions, it can be concluded that learning is an interaction between two parties, namely between educators and students, where an educator gives lessons or new things to students gradually until they can think, trying to get the knowledge they call themselves 11 . This learning can be done anywhere as long as the environment and material are delivered to build students' enthusiasm.…”
Section: Learning Conceptmentioning
confidence: 99%